Employee Relationship Management and Employee Performance: An Impact Study - Shisir Kumar Mohapatra; Dr. Sadananda Sahoo; Dr. Santanu Kumar Das (Srusti Management Review, 2025)
The current research investigates the relationship between employee relationship management (ERM), job satisfaction, job involvement, and organizational effectiveness from an emerging market perspective. To empirically test the hypothesized model, we conducted SEM analysis on 458 opinion survey responses collected from steel manufacturing units in India. As a whole, the research results show that ERM has a strong and positive effect on job satisfaction and job involvement. In addition, the ERM to employee performance relationship was one of the positive and statistically significant pathways established. The study further determined the effect of job satisfaction and job involvement as potential moderators. The results enrich the knowledge on the phenomena. Also, the results assist HR managers and policy makers to formulate more effective strategies aimed at using employee relationship-building mechanisms for organizational process facilitation.